Europeanization – a conceptual frame for local government studies? - Lackowska-Madurowicz, Marta (Journal of Public Governance, 2012)
Given that the Europeanization concept is not very popular in Polish studies on self-government, the authors decided to discuss its theoretical foundations. They start with a brief overview of definitions, drawing attention to the multiplicity of approaches and attitudes. Their evolution is presented against a wider background of numerous theoretical perspectives developed in European studies. An important part of the paper is the presentation of critical views on Europeanization: its most frequently contested elements as well as challenges formulated by the scholars who research it. The main objective of the paper is to develop a missing link between the concept and the policies of self-government units. Until now, the concept of Europeanization has been used above all in research on the national level,sometimes referring also to regions and cities. Its application to local government studies requires its modification, the outline of which is presented in the paper.